Simultaneous Encapsulation of Probiotic Bacteria (Lactococcus lactis, and Lactiplantibacillus plantarum) in Calcium Alginate Hydrogels - Marko Vinceković; Luna Maslov Bandić; Fabijan Oštarić; Marta Kiš; Nevijo Zdolec; Ivan Marić; Suzana Šegota; Hana Zelić; Nataša Mikulec (Gels)
Encapsulation in alginate hydrogel microspheres is an effective method for protecting and improving the survival of lactic acid bacteria in different environments. This research aims to expand the knowledge about the structure/property relationship of calcium alginate microspheres loaded with a mixture of autochthonous probiotic bacteria (Lactococcus lactis and Lactiplantibacillus plantarum). A novel hydrogel formulation (FORMLAB) was prepared by ionic gelation and the molecular interactions between the FORMLAB constituents, surface morphology, structure, swelling degree, and release profile were characterized. The simultaneous encapsulation of two bacterial cultures in the same compartment does not diminish their viability. The binding of calcium ions to bacterial cells creates favorable conditions for the propagation of the encapsulated bacteria. The molecular interactions between the FORMLAB constituents are complex, involving mainly hydrogen bonds and electrostatic interactions. With a very high degree of swelling followed by low crosslinking, the surface of the microspheres covered with bacterial cells and diffusion through the hydrogel matrix allow for the delivery of probiotics at the right time. The findings suggest that bacterial cells are efficiently delivered from calcium alginate microspheres, offering promising applications in the development of functional foods, especially in cheese production.